Applying Contextual Teaching and Learning (Ctl) Strategy to Improve Simple Past Tense of the Ninth Grade Students of MTS. Al-Khairaat Tondo: Penerapan Strategi Contextual Teaching and Learning (Ctl) untuk Meningkatkan Simple Past Tense Siswa Kelas IX MTS. Al-Khairat Tondo - I Made Winaya; Muh. Asri Hente; Abdul Waris (Universitas Muhammadiyah Palu, 2021)
The students of MTs. Al-Khairaat Tondo had a problem in simple past tense; namely, they had low understanding in simple past tense. This research aims at finding out whether applying Contextual Teaching and Learning (CTL) Strategy is effective to improve the understanding of ninth grade students of MTs. Al-Khairaat Tondo in simple past tense. This is a quasi-experimental research design. Its sample was 18 for grade IXB and 20 for grade IXC which were selected randomly. Its data is collected through a test (pre-test and post-test). Pre-test was conducted to know the students’ prior knowledge before treatment, while the post-test was conducted to measure their understanding after treatment. These data were analyzed statistically. The result of this research indicates that the t-counted was 0,45. The researcher found that the t-table was 0,329 by applying 0,05 level of significance and 36 degrees of freedom. T-counted value was higher than t-table value. It means the research hypothesis is accepted. In other words, applying Contextual Teaching and Learning Strategy can improve students’ understanding in simple past tense.